Pendampingan Peningkatan Pemahaman Produk dan Pengembangan Bisnis Anggota Koperasi di Kabupaten Semarang - Natoil, Natoil; Sundari, Pipit; Junedi, Achmad (Jurnal Penelitian dan Pengabdian Masyarakat, 2024)
This community service is carried out to provide vocational training and assistance for cooperative members as well as cooperative managers in Semarang Regency. This training aims to increase the understanding of cooperative members and cooperative managers regarding the products they have and strategies for developing their business. This includes a deeper understanding of the important aspects of running their business ventures. The method used in this training is an interactive training approach which includes theory delivery, group discussions and case studies with the aim of deepening understanding through constructive interactions and practical application of the concepts taught. The findings in this community training show a significant increase in cooperative members' understanding of the products and business development of their cooperative members after the training was completed. The results of the training show that training participants increasingly understand and are able to implement new strategies in their business, improve product quality, and design more effective marketing strategies. The conclusions of this research confirm that training focused on developing business skills is able to have a significant positive impact on cooperative members, increasing their ability to manage business effectively and sustainably.